Aversive responses of captive sandbar sharks Carcharhinus plumbeus to strong magnetic fields - Siegenthaler, A.; Niemantsverdriet, P. R. W.; Laterveer, M.; Heitkönig, I. M. A. (Journal of fish biology, 2016)
This experimental study focused on the possible deterrent effect of permanent magnets on adult sandbar sharks Carcharhinus plumbeus. Results showed that the presence of a magnetic field significantly reduced the number of approaches of conditioned C. plumbeus towards a target indicating that adult C. plumbeus can be deterred by strong magnetic fields. These data, therefore, confirm that the use of magnetic devices to reduce shark by‐catch is a promising avenue.